Conference program: AGU hydrology days 2003 - Ramírez, Jorge A., editor; American Geophysical Union, author; Colorado State University, author; Colorado State University, publisher (Colorado State University. Libraries, 2003)
23rd annual AGU hydrology days was held on March 31-April 2, 2003 at Colorado State University. To access abstracts, please see: http://hydrologydays.colostate.edu/schedule_03.htm.
Hydrology days 2003
AGU hydrology days 2003
Keywords: Hydrology -- Congresses